A transcendência poética em Gilberto Mendonça Teles sob a perspectiva de Gaston Bachelard - Borba, Sônia Mariz (2014)
This dissertation proposes a study of the lyric from Gilberto Mendonça Teles and has the goal of show the importance of image and imagination in the creative process of his lyric below the point of view of phenomenology of Gaston Bachelard . For this phenomenologist the poetic image is a new being of language that deeply enlightens our conscience, making the literary creation one of the destinations of the word. This makes the poet is seen as a special issuer, whom diction opens a future of language. The poetic image is established as a kind of valve that releases the perception and provides deep dazzle to the reader, for it is through the imagination that our souvenirs are rebuilt in discontinuous and lacunar temporal movements, providing us,through the work of art, the insertion in the creative moment of revival.The necessary theoretical basis for this work was also based on studies of lyrical from Octavio Paz, which deals with significant multiple faces of the poetic word. These studies assumed a gloomy and unprecedented universe in which the unpredictable meanings are established in the interstices between words. Thus, we seek to show the poetic transcendence in lyric of Gilberto Mendonça Teles, from reverie and expressive power of images that allow the poet a dilation of the semantics of the words, so that they are able to reveal the essence of the lyric voice transformed into language.